Creative consulting : innovative perspectives on management consulting - Buono, Anthony F. (Research in management consulting., 2004)
Buono (Bentley College) collects material on changes in the management consultant industry, current trends and techniques in management consulting, and concepts of consulting theory building and intervention. Contributors in business administration, strategic management, and organizational change offer perspectives on the various ways in which consultants and their firms are attempting to position and reposition themselves as leading professionals, and address topics in linkage research, global virtual teams, and executive coaching.